Apa Yang Menahan Manusia Durhaka” Dalam 2 Tesalonika 2:6? - Diyestri Ariyani Sekekere; Agustinus Faot; Jonathan Octavianus (Jurnal Teologi dan Pelayanan Kerusso, 2023)
This article addresses various theological debates regarding "what restrains the wicked." The article argues that Paul's expression regarding what restrains the wicked is a repetition of information from 1 Thessalonians 1:5, mentioning the term πνεύματι ἁγίῳ (Holy Spirit) as a source of enduring strength throughout the history of the church. To substantiate this claim, the article employs an exegetical method and employs two steps of the exegetical method, namely Contextual Analysis and Grammatical Analysis. Based on the contextual and grammatical analysis, the article concludes that "What Restrains" in 2 Thessalonians 2:6 refers to the Holy Spirit. This is supported by the fact that the Person of the Holy Spirit is repeatedly conveyed to the church in the first and second letters as a powerful entity to encourage the ministry spirit of the Apostle Paul and to provide strength to the congregation, including restraining the wicked. Abstrak Indonesia Artikel ini menjawab berbagai perdebatan teologis tentang "apa yang menahan manusia yang durhaka." Artikel ini berpendapat bahwa pernyataan Paulus tentang apa yang menahan manusia yang durhaka adalah pengulangan informasi dari 1 Tesalonika 1:5 yang menyebutkan istilah πνεύματι ἁγίῳ (Roh Kudus) sebagai sumber kekuatan yang kokoh sepanjang sejarah gereja. Untuk membuktikan pandangan ini, artikel ini menggunakan metode eksegesis dan melibatkan dua tahap dari metode eksegesis, yaitu Analisis Konteks dan Analisis Gramatikal. Berdasarkan hasil analisis konteks dan gramatikal, artikel ini menyimpulkan bahwa "Apa yang Menahan" dalam 2 Tesalonika 2:6 adalah Roh Kudus. Hal ini didasarkan pada fakta bahwa Pribadi Roh Kudus secara berulang kali disebutkan dalam surat pertama dan surat kedua kepada jemaat sebagai pribadi yang kuat untuk memotivasi pelayanan Rasul Paulus dan memberikan kekuatan kepada jemaat, termasuk dalam menahan manusia yang durhaka.